The Effect Of Dietary Crude Palm Oil And Alphatocopheryl Acetate On Reproductive Performance And Larval Quality Of Tilapia (Oreochromis sp.) - Wang, Yan (2014)

(untitled)
The present dissertation was conducted to investigate effects of the broodstock dietary lipids and vitamin E on the reproductive performance of tilapia and the quality of larvae hatched. Four isonitrogenous (35% protein) and isolipidic (10%) caseinbased diets were formulated with added fish oil (FO), FO and crude palm oil (FO+CPO; 1:1), CPO or linseed oil as the lipid source in Experiment 1, and supplemented with 0 (T0), 60 (T60), 600 (T600) mg α-tocopheryal acetate, or a CPO-derived tocotrienolsrich fraction designated to provide α-tocopherol at a level of 60 (PalmE60) mg per kg dry diet in Experiment 2. Disertasi in dijalankan untuk menyiasat kesan-kesan pemakanan lipid dan vitamin E induk kepada prestasi pembiakan tilapia dan kualiti larva. Empat diet yang isonitrogenus (35% protein) dan isolipidik (10%) berasaskan kasein dirumuskan dengan minyak ikan (FO), FO dan minyak kelapa sawit mentah (FO+CPO; 1:1), CPO atau minyak linseed sebagai sumber lipid dalam Eksperimen 1, dan 0 (T0), 60 (T60), 600 (T600) mg α-tokoferil asetat, atau pecahan kaya tokotrienol berasaskan CPO yang ditetapkan untuk menyediakan α-tokoferol pada tahap 60 (PalmE60) mg sekilogram diet kering ditambah dalam Eksperimen 2.